Effect of Virtual Reality Simulation: “Urinary Catheterization Skills” on Nursing Students’ Self-Confidence - Marshanda Syaharani Putri; Iqbal Pramukti; Desy Indrayani; Restuning Widiasih (Universitas Padjadjaran, 2023)
Confidence is essential for nursing students in producing better practice of nursing action skills, so this needs to be supported by good learning media. One of the learning media currently developing is virtual reality simulation, an interactive learning media based on immersive technology that combines real space (reality) with virtual space (virtual). This study aimed to analyze the effect of virtual reality simulation in urinary catheterization on the self-confidence of nursing students. This study used a pre-experiment design with a one-group pretest-posttest design approach. Self-confidence was measured using The Confidence Scale questionnaire, consisting of five items. The sampling technique uses a purposive sampling technique with a minimum total sample is 49 students. The data collected were analyzed using the non-parametric Wilcoxon signed-rank test. The result showed an increase in the mean value in the post-test results (21.65) compared to the pretest results (16.98), with an average increase of 4.67 points. The statistical test results showed a significant difference after using virtual reality simulation on nursing students' confidence (p <0.05). So, virtual reality simulation is a learning media that influences nursing students' confidence in performing urinary catheterization skills.